Breaking the Barriers of Zakat Payment in Zakat Institutions: An Analysis of Muslim`s Reluctance - Razak, Syaparuddin; Raking, Jumriani; Rahmawati, Anita (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
This study aims to comprehensively understand the factors that shape reluctance toward zakat payment in zakat institutions among Muslims, addressing a significant research gap. To achieve this, the study identifies and addresses barriers hindering zakat payment in these institutions. Employing a modified TPB (Theory of Planned Behavior) framework tailored to the context of reluctance, the study employs SmartPLS (v. 4.0.8.9) software for analysis, based on 303 online survey responses. The study reveals the impactful influence of negative attitude, low subjective norms, and low confidence on Muslim`s reluctance to pay zakat in zakat institutions, while the absence of proper socialization does not exhibit a similar effect. Moreover, the research validates the impact of low confidence and weak intention on Muslim`s reluctance to pay zakat. The mediating role of weak intention in the relationship between negative attitude, low subjective norms, and low confidence level, shapes Muslim`s reluctance to pay zakat. The findings highlight the need for targeted interventions, encompassing educational campaigns, community engagement, and self-development initiatives, to foster positive attitudes and confidence, thereby enhancing zakat compliance.